Efficient Pb (II) removal from wastewater by TEG coated Fe3O4 ferrofluid - Sajjad Lotfi; Bagher Aslibeiki; Mahmoud Zarei (Journal of Water and Environmental Nanotechnology, 2021)
Tri-ethylene glycol (TEG) coated Fe3O4 nanoparticles ferrofluid were used for Pb (II) removal from simulated wastewater. The samples were synthesized using a modified co-precipitation method. The prepared samples were characterized by different techniques including X-ray diffraction, Rietveld method, FTIR, FESEM, TEM, VSM, TGA, BET and atomic adsorption experiments. The crystallinity of nanoparticles with a cubic spinel ferrite structure and absence of impurity phases were verified using X-ray diffraction and Rietveld method. The presence of TEG was approved by FTIR and thermogravimetric analysis. The VSM results showed that the bonding between the TEG molecules and ferrite nanoparticles, reduces the surface spin disorder, influences the morphology and magnetization, and consequently increases the Pb (II) removal efficiency to a high value of 97%. The obtained high value of adsorption capacity of q=363.4 mg.g-1 with R= 91 % and q=129.4 mg.g-1 with R=97 %shows effective role of TEG coating on Pb (II) adsorption. The interesting results of this study imply that the TEG coated ferrofluid sample is suitable candidate for practical applications.